2018
DOI: 10.1007/s12020-018-1532-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin D supplementation on thyroid autoantibody levels in the treatment of autoimmune thyroiditis: a systematic review and a meta-analysis

Abstract: The current evidence suggests that vitamin D supplementation could decrease serum TPO-Ab and Tg-Ab titers of patients with AIT in the short-term (about six months). More high quality studies are needed to further confirm the effects, especially the long-term effects of Vitamin D supplementation on thyroid autoantibodies levels in the treatment of AIT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 29 publications
5
39
0
1
Order By: Relevance
“…In a systematic review and meta-analysis, Wang et al concluded that supplementation with VitD appeared to significantly reduce levels of anti-TPO (for treatments ≥6 months) and anti-Tg, with no reported serious adverse effects [97]. More recently, Koehler et al retrospectively analyzed 933 patients with autoimmune thyroiditis and found a greater reduction in anti-TPO levels in a 58-patient sub-group that had an improvement in their initially insufficient VitD level (<30 ng/mL) vs. a control group that maintained a VitD level below the threshold.…”
Section: Relevance Of Supplementationmentioning
confidence: 99%
“…In a systematic review and meta-analysis, Wang et al concluded that supplementation with VitD appeared to significantly reduce levels of anti-TPO (for treatments ≥6 months) and anti-Tg, with no reported serious adverse effects [97]. More recently, Koehler et al retrospectively analyzed 933 patients with autoimmune thyroiditis and found a greater reduction in anti-TPO levels in a 58-patient sub-group that had an improvement in their initially insufficient VitD level (<30 ng/mL) vs. a control group that maintained a VitD level below the threshold.…”
Section: Relevance Of Supplementationmentioning
confidence: 99%
“…[48] In a meta-analysis comprising of 6 RCTs and involving 344 patients with AITD, Vitamin D supplementation was associated with significant reductions in TPOAb and TgAb titers at 6 months follow-up. [49] In a RCT involving 251 apparently healthy individuals, low dose vitamin supplementation (400 IU/day and 1000 IU/day) as compared to placebo did not result in any significant change in TPOAb and TSH titers at 16 weeks of follow-up. [50] Limitations of this study include the fact that most of the patients in these studies were healthy individuals without AITD and had TPOAb titers in the normal range.…”
Section: Resultsmentioning
confidence: 99%
“…A recent meta-analysis including 6 RCT conducted by Wang et al in patients with AITDs found that 6-months VD supplementation significantly decreased TPO-Ab (3 studies, standardized mean difference [SMD]: -1.11, 95% CI -1.52 to -0.70, P <0.01) and TG-Ab titers (SMD: -0.12, 95% CI: -0.69 to 0.44, P = 0.67) compared with controls [38].…”
Section: Vitamin D Supplementation Thyroid and Immune Functions In Hmentioning
confidence: 98%